A formação humana em Goethe na obra : Os anos de aprendizado de Wilhelm Meister - Marangon, Marcio Luis (2018)
The research from the text had as objective to reflect on the concept of formation in Johann Wolfgang von Goethe, having as reference the work the Years of learning of Wilhelm Meister. The guiding question of the investigation received the following formulation: what is nuclear in the concept of formation of Goethe? The guiding hypothesis considers that in seeking an omnipolar and all-encompassing formation, based on self-formation, Goethe manages to unify aspects of Romanticism and Enlightenment, thus forming a comprehensive concept regarding the formation of individuals and thus contributing to the training at different times, including current events. It is a work of predominantly analytical-hermeneutic methodology, which seeks to make explicit the universally valid rules of comprehension present in Goethe's work and which make possible the current conception of formation. The work is organized in six chapters. The first one analyzes the life of Johann Wolgang von Goethe, presenting aspects of his family life, his relations, the influences of research and training he received, as well as parts of his intellectual trajectory to the description of what led him to constitute the work under analysis. For this, the works of Goethe interpreters and also of the author's biographers, such as Citati (1996), Lukacs (1968), Eckermann (1950), Benjamin (2009) and Simmel (2005a) were analyzed. The second chapter discusses chronologically the construction of Goethe's formative experience, with a cut of the thinkers who had a clear influence on the constitution of the work analyzed: Herder, Rousseau, Espinoza, Kant, Shakespeare. The third chapter focuses on the "technical and structural" constitution of the work, addressing - through classical authors such as Auerbach (1976) and Bakhtin (2012) - the history of the constitution of the work, the genre chosen and worked by Goethe, and the main criticisms that the work received. Chapters four and five are reserved for a detailed and in-depth analysis of the eight books and their main characters, with the main purpose of clarifying the concept of formation on which Goethe sought to form himself and to form a cultured nation. The ending is an attempt, reflecting on what was addressed in the previous chapters, to define what can be considered nuclear in the concept of formation in The Years of Learning by Wilhelm Meister. In the final considerations, the productivity of the conception of formation - Bildung - is analyzed in Goethe for the present, emphasizing three aspects: the criticism to bourgeois education and the limits of the purely technological formation; autonomy and self-cultivation, starting from the very nature of individuals; and omnilaterality as a formation that expresses itself through a work of understanding and transforming oneself and, at the same time, transforming the world. In all these aspects are indicated the basic assumptions to dialogue with the different epochs, including the actuality.